2011
DOI: 10.1007/s11434-011-4471-6
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the brominated flame retardant tris-(2,3-dibromopropyl) isocyanurate in zebrafish (Danio rerio)

Abstract: Tris-(2,3-dibromopropyl) isocyanurate (TBC) is a heterocyclic brominated flame retardant that was recently detected in the environment in China. TBC is semi-volatile and can accumulate in the lipid of some species, but little is known about its effect on aquatic organisms. We exposed adult zebrafish to 0, 0.25, 1 and 4 mg/L TBC for 28 d and measured the effect on survival, growth, histopathology, hormone levels, enzyme activity, and gene expression. TBC exposure had no effect on survival or growth. We observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…In vitro study indicated that TBC might be one of the causative compounds inducing neuronal toxicity in the environmental samples collected near a TBC production facility (Qu et al 2011). Also, TBC has been shown to remarkably inhibit estrogen-dependent vitellogenin (VTG) gene expression in liver and further affect gonadal development in both male and female zebrafish (Zhang et al 2011). Therefore, these initial results indicate that TBC may have endocrine-disruptive effects and interference with the hormonal balance, resulting in developmental and reproductive abnormalities.…”
Section: Introductionmentioning
confidence: 95%
“…In vitro study indicated that TBC might be one of the causative compounds inducing neuronal toxicity in the environmental samples collected near a TBC production facility (Qu et al 2011). Also, TBC has been shown to remarkably inhibit estrogen-dependent vitellogenin (VTG) gene expression in liver and further affect gonadal development in both male and female zebrafish (Zhang et al 2011). Therefore, these initial results indicate that TBC may have endocrine-disruptive effects and interference with the hormonal balance, resulting in developmental and reproductive abnormalities.…”
Section: Introductionmentioning
confidence: 95%
“…TBC exposure disrupts the development and endocrine of zebrafish embryo, damages their mitochondria and interferes in their gas bladder inflation Zhang et al, 2011). It has been speculated to be toxic to neuronal cells (Qu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, halogenated flame retardants have been widely used in large volumes as additive in household products for fire safety reasons due to their excellent capability to reduce flammability. However, increasing concerns have also been raised on the environment problems caused by them, especially for brominated flame retardants (BFRs) which are widely applied to a variety of combustible materials to reduce the risk of fire damage [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that TBC is semi-volatile, environmentaly persistent and has a tendency to bioaccumulate. It can be accumulated in lipid-rich organs, such as the brain, liver, intestine, etc [4]. In 2009, TBC was found, for the first time, in the natural environment around a TBC manufacturing plant in South China [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation